Kesesuaian atau Sekadar Formalitas? Analisis Implementasi Standar ISSB dalam Integrated Reporting Perusahaan di Indonesia - Jainal Arifin; Yusnaini Yusnaini (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to analyze the relationship between the International Sustainability Standards Board (ISSB) and Integrated Reporting in improving the quality, transparency, and comparability of corporate sustainability reporting. Using a qualitative approach with the Systematic Literature Review method, this study examines 29 Scopus-indexed articles published during 2022–2026. The findings indicate that ISSB, through IFRS S1 and IFRS S2, plays an important role in harmonizing global sustainability reporting standards and integrating financial with non-financial information, while Integrated Reporting strengthens stakeholder understanding of long-term value creation. High-quality sustainability disclosure is also associated with better accounting information quality, firm value, investment decisions, and sustainable growth. However, several challenges remain, including selective disclosure, limited assurance quality, data readiness issues, and institutional capacity gaps, especially in emerging economies. In Indonesia, successful ISSB adoption requires regulatory support, professional competence, and alignment with the national reporting ecosystem. Overall, this study confirms that the effectiveness of ISSB and Integrated Reporting depends not only on standards availability, but also on governance quality, external assurance, and corporate commitment to sustainability accountability.